The dynamic association between ovariole loss and sterility in adult honeybee workers - Ronai, Isobel (Proc Biol Sci, 2017)
In the social insects, ovary state (the presence or absence of mature oocytes) and ovary size (the number of ovarioles) are often used as proxies for the reproductive capacity of an individual worker. Ovary size is assumed to be fixed post-eclosion whereas ovary state is demonstrably plastic post-eclosion. Here, we show that in fact ovary size declines as honeybee workers age. This finding is robust across two honeybee species: Apis mellifera and A. cerana. The ovariole loss is likely to be due to the regression of particular ovarioles via programmed cell death. We also provide further support for the observation that honeybee workers with activated ovaries (mature oocytes present) most commonly have five ovarioles rather than a greater or smaller number. This result suggests that workers with more than five ovarioles are unable to physiologically support more than five activated ovarioles and that workers with fewer than five ovarioles are below a threshold necessary for ovary activation. As a worker's ovariole number declines with age, studies on worker ovariole number need to take this plasticity into account.